SELF-DIRECTED LEARNING AND MOOC INTEGRATION INTO HIGHER EDUCATION EFL CLASSROOMS - Ersoy, Nazife Sen; Dogan, Yunus (Anadolu Univ, 2023)
This research includes the first cycle of an application based on the integration of a MOOC given in the field of writing into the formal education curriculum to reinforce classroom teaching and support the learning process to improve English writing skills. It was carried out in the spring semester of the 2021-2022 academic year with 14 students studying in an English preparatory program at a Turkish state university. In this study, qualitative research method was adopted and the action research design was applied. The implementation was carried out within the scope of the Reading/Writing course in the program in question. As data collection tools, a semi-structured interview form, Self-directed Learning Scale, and students' course completion scores in their chosen MOOCs were utilized. In addition, the articles written by the students at the end of the term within the scope of classroom evaluation were also used to support the research data. The first data obtained in this direction show that the majority of the participants could not go beyond the course selection and registration stage. Although the students mostly did not have problems in accessing technology and showed self-directed learner characteristics, they did not follow or complete these courses due to lack of motivation, technological problems, heavy course loads and health problems.
Keywords: MOOC; foreign language learning; writing skill; preparatory program; university students.